THE INFLUENCE OF PESANTREN TRADITION ON ARABIC LANGUAGE LEARNING IN ISLAMIC SCHOOLS - Maya Aulia; Ika Supriyanti (STIT Pringsewu, 2025)
This study investigates the integration and impact of traditional pesantren pedagogical methods on Arabic language instruction within Indonesia's modern Islamic school system. Employing a qualitative research design based on a comprehensive literature review, the research examines how practices such as sorogan, bandongan, and halaqah influence student proficiency, particularly in classical textual comprehension and memorization. The findings reveal that while these traditional methods significantly enhance reading and interpretative skills, they often fall short in developing communicative competence. The study provides a comparative analysis of pesantren-based and modern pedagogical approaches, concluding with a discussion of the potential for a hybrid model that balances the strengths of both traditions to improve overall Arabic language education in Indonesia.